Hazardous geomorphic processes in the extratropical Andes with a focus on glacial lake outburst floods - Iribarren Anacona, Pablo (11708465) (2016)
This study examines hazardous processes and events originating from glacier and permafrost areas in the extratropical Andes (Andes of Chile and Argentina) in order to document their frequency, magnitude, dynamics and their geomorphic and societal impacts. Ice-avalanches and rock-falls from permafrost areas, lahars from ice-capped volcanoes and glacial lake outburst floods (GLOFs) have occurred in the extratropical Andes causing ~200 human deaths in the Twentieth Century. However, data about these events is scarce and has not been studied systematically. Thus, a better knowledge of glacier and permafrost hazards in the extratropical Andes is required to better prepare for threats emerging from a rapidly evolving cryosphere. I carried out a regional-scale review of hazardous processes and events originating in glacier and permafrost areas in the extratropical Andes. This review, developed by means of a bibliographic analysis and the interpretation of satellite images, shows that multi-phase mass movements involving glaciers and permafrost and lahars have caused damage to communities in the extratropical Andes. However, it is noted that GLOFs are one the most common and far reaching hazards and that GLOFs in this region include some of the most voluminous GLOFs in historical time on Earth. Furthermore, GLOF hazard is likely to increase in the future in response to glacier retreat and lake development. To gain insight into the dynamics of GLOFs I create a regional-scale inventory of glacier lakes and associated hazards in the Baker Basin, a 20500 km2 glaciated basin in the Chilean Patagonia. I also simulate and reconstruct moraine- and ice- dammed lake failures in the extratropical Andes using numerical and empirical models. More than 100 GLOFs have occurred in the extratropical Andes since the Eighteenth Century and at least 16 moraine-dammed lakes have produced GLOFs. In the extratropical Andes most of the failed moraine-dammed lakes were in contact with retreating glaciers and had moderate (> 8°) to steep (>15°) outlet slopes. Ice-dammed lakes also produced GLOFs in the extratropical Andes, damaging communities and highlighting the need for a better understanding of the GLOF dynamics and hazards. Thus, I reconstruct and model GLOFs that occurred in maritime western Patagonia (Engaño Valley) and the high-arid Andes (Manflas Valley) to characterise the GLOF dynamics in these contrasting environments. Hydraulic modelling and geomorphologic analysis shows that the Engaño River GLOF (46º S) behaved as a Newtonian flow and incorporated tree trunks, from the gently sloping and heavily-forested valley, which increased the GLOF damaging capacity. In contrast, the Manflas GLOF (28º S) descended from a steep valley behaving as a sediment-laden flow, which was capable of moving boulder-size rocks dozens of kilometres from the GLOF source. In both events lack of awareness of the GLOF hazard and a lack of territorial planning accentuated the GLOF damage. These GLOF reconstructions highlight both the difficulties in modelling sediment-laden flows over long distances, and the utility of empirical debris-flow models for regional-scale hazard analysis. This thesis synthesises and increases our knowledge about the distribution, frequency, magnitude and dynamics of hazardous processes that have occurred in glacier and permafrost areas in the extratropical Andes. This knowledge forms a basis for future assessments of glacier and permafrost related hazards in the Chilean and Argentinean Andes and helps inform strategies and policies to face hazardous geomorphologic and hydrological processes emerging from a rapidly evolving cryosphere.